Genetic analysis of biochemical, fiber yield and quality traits of upland cotton under high-temperature - Abdul Manan; Muhammad Mubashar Zafar; Maozhi Ren; Muhammad Khurshid; Adeela Sahar; Abdul Rehman; Hina Firdous; Yuan Youlu; Abdul Razzaq; Amir Shakeel (Plant Production Science, 2021)
To understand the effect of heat stress on morphology and physiology of the cotton, eight cotton genotypes with their 15F1 hybrids (five lines, three testers) were grown in the field conditions under randomized complete block design (RCBD) with two treatments i.e. normal and high-temperature stresses with two replications followed by split-plot arrangement. Data were collected for biochemical and yield-related parameters. Mean values of all studied traits were reduced significantly under high-temperature stress whilst the mean value of lint%, catalase activity, total soluble proteins, peroxidase, and carotenoids were increased under high-temperature. Under both conditions, the number of bolls, boll weight, seed cotton yield, lint index, seed mass per boll, hydrogen peroxide content, catalase activity, total soluble proteins, carotenoids, and chlorophyll contents had high heritability values along with high genetic advance percent mean which revealed, these traits were controlled by additive gene action. The lint%, seed index, short fiber index, fiber strength, fiber fineness, upper half mean length and peroxidase activity had high heritability with moderate genetic advance under heat stress conditions which showed, these traits were controlled by non-additive gene action. Under both temperature conditions, FH-458, IUB-65, CRS-2, and FH-313 were good general combiners for physicochemical and yield-related traits. The cross combination of IUB-013× CRS-2 and FH-458× FH-313 were good specific combiner for plant height and seed cotton yield whilst for fiber quality and biochemical traits, the best specific combiners were VH-329× FH-313 and IUB-013× CRS-2. These identified parents and cross combinations might be used for improving already present commercial varieties under high-temperature stress.